Fluvial-aeolian sedimentary facies, Sossusvlei, Namib Desert. Issue 2 (13th November 2018) - Feder, Amelie; Zimmermann, Robert; Stollhofen, Harald; Caracciolo, Luca; Garzanti, Eduardo; Andreani, Louis
ABSTRACT: Aeolian sedimentary processes and corresponding facies shape the Earth's surface and control the evolution of dune fields. The Namib Sand Sea with its Sossusvlei playa-lake is a perfect example to investigate the spatial distribution of fluvially influenced aeolian deposits. Remote sensing in combination with ground observations allowed for mapping of the facies distribution pattern of associated fluvial and aeolian sediments. Laboratory spectral signature measurements were used to further improve the separation between six groups of facies: modern aeolian sand, deflation surface, mud pool/mud drapes, heavy mineral lag, reworked fluvial–aeolian sediments, and fossil dune remnant. The best results were achieved through a supervised classification algorithm trained by field observations, a combination of Principal Component Analysis, band ratios, texture and geomorphologic indices. Consequently, a map outlining the facies distribution pattern of the Sossusvlei area at a scale of 1:10, 000 was created. We propose this as a possible workflow to efficiently map and monitor desert environments and to investigate the interplay of aeolian and fluvial sediments.